Asuhan Keperawatan pada Pasien Gagal Ginjal Kronis di RSUD Bukittinggi Tahun 2024 - Sonya Firaya; Aini Yusra; Yulvi Hardoni (CV CENDIKIA JENIUS INDONESIA, 2026)
Chronic Kidney Disease (CKD) is a growing health problem with a significant increase in prevalence, both nationally and specifically in West Sumatra Province. CKD has a considerable impact on patients' quality of life and requires comprehensive and continuous nursing care.This study aims to describe the implementation of nursing care for patients with chronic kidney disease at Dr. Achmad Mochtar Regional Hospital Bukittinggi in 2024. This research used a descriptive design with a case study approach. The subject was a stage V CKD patient treated in the Internal Ward of Dr. Achmad Mochtar Hospital. Data were collected through interviews, physical examinations, and standard nursing assessments. The nursing process was applied, including assessment, diagnosis, intervention, implementation, and evaluation.The assessment found that the patient experienced shortness of breath, nausea, vomiting, loss of appetite, and edema. The main nursing diagnoses were ineffective breathing pattern, hypervolemia, and activity intolerance. Nursing interventions such as deep breathing exercises were effective in reducing shortness of breath. Evaluation showed improvement in the patient’s respiratory pattern.Well-planned and targeted nursing care can help address the main problems in CKD patients. Well-planned and targeted nursing care can help address the main problems of CKD patients